Increasing the flame resistance of cellulose by nonthermal plasma coupled with chemical treatments - Hoang Tung Do; Duc Ba Nguyen; Thi Hoai Phuong Nguyen; Thi Thu Huong Le; Thi Thu Thuy Nguyen (Applied Physics Express)
Nonthermal plasma coupled with H _2 O _2 and HBO _3 treatment was examined to enhance cellulose flame resistance (FR) through the plasma-liquid interaction (PLI) of the H _2 O _2 solution (indirect method) and plasma-activated surface (PAS) by Ar plasma jet (direct method). Here, the results revealed a significant increase in cellulose FR of up to 48% with plasma treatments, depending on flame exposure time and synthesized procedures. This enhancement is attributed to the changes in the chemical compositions and cellulose surface by plasma treatment, improving boron distribution on the cellulose surface during HBO _3 treatment. Compared to the PLI, PAS demonstrated superiority in increasing FR and offered greater economic efficiency by a short treatment time of 1 min.